1998
DOI: 10.1046/j.1432-1327.1998.2540230.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐regulatory protein‐1 (IRP‐1) is highly conserved in two invertebrate species

Abstract: Iron-regulatory protein-1 (IRP-1) plays a dual role as a regulatory RNA-binding protein and as a cytoplasmic aconitase. When bound to iron-responsive elements (IRE), IRP-1 post-transcriptionally regulates the expression of mRNAs involved in iron metabolism. IRP have been cloned from several vertebrate species. Using a degenerate-primer PCR strategy and the screening of data bases, we now identify the homologues of IRP-1 in two invertebrate species, Drosophila melanogaster and Caenorhabditis elegans. Comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Since members of both aconitase subfamilies were identified in invertebrates, e.g. Caenorhabditis elegans and Drosophila melanogaster (73), specialization of mitochondrial and cytoplasmic aconitase functions seems to have occurred early during animal evolution. Here we report on a protozoan aconitase which belongs to the IRP-1 subfamily but localizes in the mitochondrion as well as in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Since members of both aconitase subfamilies were identified in invertebrates, e.g. Caenorhabditis elegans and Drosophila melanogaster (73), specialization of mitochondrial and cytoplasmic aconitase functions seems to have occurred early during animal evolution. Here we report on a protozoan aconitase which belongs to the IRP-1 subfamily but localizes in the mitochondrion as well as in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…elegans-The C. elegans genome possesses two aconitase genes, which are designated gei-22/aco-1 and aco-2. gei-22/ aco-1 encodes a protein that shares ϳ63% identity with mammalian IRP-1 (16), D. melanogaster IRP-1A and 1B (16), and A. thaliana (13) and T. brucei (17) IRP-1s while sharing only ϳ24% identity to porcine (28) and C. elegans mitochondrial aconitases ( Fig. 1).…”
Section: Cloning and Expression Of A Gei-22/aco-1 Homolog Inmentioning
confidence: 99%
“…IRP-1s have been identified in a wide variety of organisms, including bacteria (10 -12), plants (13)(14)(15), and animals (16,17). IRP-1s share a high degree of amino acid identity among different species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no IRE is present in Fer2LCH mRNA . IRP homologs are expressed in the fly (Muckenthaler et al 1998), and one homolog (IRP-1A) has been shown to bind to IREs from both Drosophila and mammals (Lind et al 2006).…”
mentioning
confidence: 99%